2014
DOI: 10.1007/s10334-014-0449-0
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric velocity measurements in restricted geometries using spiral sampling: a phantom study

Abstract: Object:To evaluate the accuracy of maximum velocity measurements using volumetric phase contrast imaging with spiral readouts in a stenotic flow phantom. Materials and Methods:In a phantom model, maximum velocity, flow, pressure gradient and streamline visualizations were evaluated using volumetric phase contrast MRI with velocity encoding in one (extending on current clinical practice) and three directions (for characterization of the flow field) using spiral readouts.Results of maximum velocity and pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…However, the flow rate estimates seem to be less accurate when the estimation is performed in the region of the post-stenotic flow jet, especially for the OBL orientations. This corresponds well to previous observations of flow rate measured with 4D flow spiral measurements in jet regions (15). For 2D through-plane PC-MRI, a TE longer than 3 ms has been shown to cause severe underestimation of flow rate for actual flow rates over 300 mL/s (8).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the flow rate estimates seem to be less accurate when the estimation is performed in the region of the post-stenotic flow jet, especially for the OBL orientations. This corresponds well to previous observations of flow rate measured with 4D flow spiral measurements in jet regions (15). For 2D through-plane PC-MRI, a TE longer than 3 ms has been shown to cause severe underestimation of flow rate for actual flow rates over 300 mL/s (8).…”
Section: Discussionsupporting
confidence: 90%
“…Instead, we see a slight increase of the measurement of the maximum velocity in the jet for the oblique orientation. Measurements with spiral readouts on a similar phantom have shown that a TE longer than 3 ms will result in less accurate maximum velocity estimates . In the present work, TE was 1.9–2.5 ms and 4.3–4.5 ms for the spiral and Cartesian maximum velocity measurements, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Other methods that have adopted a stack of spirals for 4D flow acquisitions include Nilsson et al . In this work, which was tested under steady‐flow phantom experiments, velocities from MRI were compared to CFD simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Spiral MRI has previously been used for 2D flow imaging , 3D MR angiography , and 2D myocardial phase velocity mapping . In addition to reducing the scan time, spiral k‐space trajectories also are inherently insensitive to flow‐induced displacement . Moreover, because spiral k–space trajectories start in the center of k‐space, they may be suitable for respiratory self‐gating.…”
Section: Introductionmentioning
confidence: 99%